Ceramic Materials Progress in Modern Ceramics - Shi, Feng (IntechOpen, 2012)
This text covers ceramic materials from the fundamentals to industrial applications. This includes their impact on the modern technologies, including nano-ceramic, ceramic matrix composites, nanostructured ceramic membranes, porous ceramics, and the sintering theory model of modern ceramics.